2008
DOI: 10.1007/s00383-008-2231-8
|View full text |Cite
|
Sign up to set email alerts
|

Transanal mucosectomy for endorectal pull-through in Hirschsprung’s disease: comparison of abdominal, extraanal and transanal approaches

Abstract: EPT with perineal approaches is less invasive and can provide a better clinical outcome than EPT with AB in terms of postoperative soiling. Compared with EA and TA, EA tended to develop stagnant enteritis or residual constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 12 publications
1
24
1
1
Order By: Relevance
“…Interestingly, continence score was significantly poorer after TEPT when compared with LEPT. In a small retrospective series of 8 TEPT patients and 20 LEPT patients, there was no soiling in the TEPT group compared with 45% soiling after LEPT [2].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Interestingly, continence score was significantly poorer after TEPT when compared with LEPT. In a small retrospective series of 8 TEPT patients and 20 LEPT patients, there was no soiling in the TEPT group compared with 45% soiling after LEPT [2].…”
Section: Discussionmentioning
confidence: 87%
“…Long-term functional results after TEPT are sparsely documented [2,[6][7][8][9]. One study reports more incontinence after TEPT than after abdominal mobilization of rectum and colon [7], whereas others present equal or even better results after TEPT [2]. Postoperative anal manometry after TEPT has demonstrated results similar to preoperative values or controls, indicating that sphincter damage after a transanal procedure was unlikely [10,11].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Interestingly, a study by Stensrud et al, which used independent examiners, showed a higher rate of long-term complications than other reports [14]. Also, different scores to assess the long-term bowel function developed by various institutions makes comparison challenging [15]. Furthermore, the outcome of the Pediatr Surg Int bowel function could be influenced by the age of the patients; if a patient is less than 4 years of age, he may not be considered continent at the time of follow-up.…”
Section: Discussionmentioning
confidence: 93%